Identification of chemical constituents in different propolis extracts and their in vitro antimicrobial activities against propionibacterium acnes and staphylococcus epidermidis : towards the development of a new formulation - T. Ismail @ T Manah, Tuan Nadrah Naim (2015)
Introduction: Propolis is a resinous material collected by the honeybees from various plant sources. The composition of propolis depends on the vegetation area and method of extraction. To date, there is no report on the chemical constituents of Apis mellifera propolis from Malaysia and their activities against acne-inducing bacteria is still lacking. Acne vulgaris is a very common skin disease and may cause permanent acne scarring and psychological morbidities such as depression, low self-esteem and unemployment. Current treatments do not achieve the optimal results and are associated with bacteria resistance or adverse effects. Objectives: This study was aimed to 1) identify the chemical constituents of water (WEP) and ethanolic extracts (EEP) of Apis mellifera propolis from the southern and northern regions of Peninsular Malaysia, 2) determine their in-vitro antimicrobial activities against acne-inducing bacteria, and 3) prepare a new topical formulation for acne. Methods: WEP and EEP were prepared and silylated compounds were identified by gas chromatography and mass spectrometry analysis. The compounds were characterised by comparison with library searches. The compounds that were present in all extracts were quantified. The extracts were then evaluated for their antimicrobial activity against Propionibacterium acnes and Staphylococcus epidermidis using agar well diffusion and broth microdilution resazurin assay. Results: Forty one individual compounds were identified and four compounds were identified for the first time from propolis which are m-salicylic acid, β-panasinsene, mannose-6-deoxy and β-DL-lyxopyranose. The main compounds identified from WEP and EEP were phenolic compounds and terpenoids, respectively. Gallic acid was found to be present in WEP and EEP from both regions. Quantification of gallic acid was performed using selected ion monitoring mode with linearity R2 > 0.995. It was found that the EEP from the northern region has the highest content of gallic acid [327.51 (SD = 14.58) μg/g, CV (%) = 4.5, n = 3]. The antimicrobial screening test showed that both microorganisms were sensitive to the all propolis extracts and gallic acid. The broth microdilution resazurin assay demonstrates that MIC values of EEP from both regions were generally lower than WEP against both acne-causing bacteria. Propionibacterium acnes was more susceptible to EEP (MIC = 0.3 to 0.6 μg/ml) when compared to Staphylococcus epidermidis (MIC = 156 to 625 μg/ml). Higher concentration of WEP is needed to inhibit acne-causing bacteria (MIC > 1 mg/ml). Gallic acid activity showed promising result against Staphylococcus epidermidis but not as good as EEP on Propionibacterium acnes. Interestingly, a new formulation showed greater zone of inhibition compared to benzoyl peroxide 10%. Conclusion: The WEP and EEP of Apis mellifera propolis from Malaysia have valuable chemical compounds and demonstrate good antimicrobial activity. The WEP may be considered as an alternative to EEP, especially when water extract application is more desirable. Further laboratory and clinical studies are needed to ascertain the use of the new propolis formulation as an alternative treatment for acne vulgaris.